PENERAPAN E-LEARNING MADRASAH DAN WHATSAPP TERHADAP AKTIVITAS DAN HASILBELAJAR BAHASA INGGRIS SISWA DI MASA PANDEMI - NINIK QODAR ISMAWARNI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
This research is a classroom action research that aims to determine the increase in activity and learning outcomes of class VII/C students of MTs Negeri Tarakan in the second semester of 2020/2021 learning English with adjectives by using madrasa E-Learning media and WhatsApp. The object of research is the activities and student learning outcomes. This research was conducted in two cycles, each cycle consisting of four stages, namely: planning, implementation, observation and reflection. Collecting data obtained from observation, interviews, documentation and tests. The data analysis technique was carried out in a descriptive way supported by qualitative and quantitative data. The results showed that the madrasa E-Learning was not optimally used as a medium for learning English for class VII/A MTs Negeri Tarakan. However, by combining the advantages of E-Learning madrasas and WhatsApp, it was found that the activities and learning scores of class VII/A students at MTs Negeri Tarakan had increased. Percentage of student activity in pre-cycle (28.3%), cycle I (70.2%) and cycle II (86.4%). The value of student learning outcomes in the pre-cycle (68.2), cycle 1 (74.7) and cycle II (78.8). Thus, the use of madrasah e-learning and WhatsApp media is able to increase the activities and learning outcomes of class VII/C students of MTs Negeri Tarakan in the 2020/2021 academic year with very good student learning activities with a percentage of learning completeness scores of 100%. ABSTRAKPenelitian ini adalah penelitian tindakan kelas yang bertujuan untuk mengetahui peningkatan aktivitas dan hasil belajar siswa kelas VII/C MTs Negeri Tarakan pada semester II tahun 2020/2021 pembelajaran Bahasa Inggris materi kata sifat dengan menggunakan media belajar e-learning madrasah dan WhatsApp. Obyek penelitian adalah aktifitas dan hasil belajar siswa. Penelitian ini dilakukan dalam dua siklus yang tiap siklus terdiri dari empat tahap, yaitu: perencanaan, pelaksanaan, obsevasi dan refleksi. Pengambilan data diperoleh dari observasi, wawancara, dokumentasi dan tes. Teknik analisis data dilakukan dengan cara diskriptif yang didukung data kualitatif dan kuatitatif. Hasil penelitian menunjukkan bahwa E-Learning madrasah kurang optimal digunakan sebagai media pembelajaran Bahasa Inggris kelas VII/A MTs Negeri Tarakan. Namun dengan memadukan kelebihan E-Learning madrasah dan WhatsApp di dapatkan bahwa aktivitas dan nilai belajar siswa kelas VII/A MTs Negeri Tarakan mengalami peningkatan. Persentase aktivitas siswa pra-siklus (28.3%), siklus I (70.2%) dan siklus II (86.4%). Nilai hasil belajar siswa pada pra-siklus (68.2), siklus 1(74.7) dan siklus II (78.8). Dengan demikian penggunaan media E-Learning madrasah dan WhatsApp mampu menaikkan aktivitas dan hasil belajar siswa kelas VII/C MTs Negeri Tarakan tahun pembelajaran 2020/2021 dengan keaktifan belajar siswa sangat baik dengan persentase nilai ketuntasan belajar 100%.